Utilization of Calcium Channel Blocker drugs (CCBs) in Serdang Hospital – retrospective study / Nordiana Shariff - Shariff, Nordiana (2016)
Introduction: Hypertension is one of the most top leading of death and it is very high prevalent in world wide’s population, mostly in geriatric. Hypertension is also one of the most costly diseases because of high health care expenditure. The utilization of antihypertensive drugs is higher and expensive. Drug utilization study can be used in providing the useful information to health care policy makers and clinicians in decision making. Objective: To describe the utilization of CCB drugs among the hypertension patients at Serdang’s Hospital.